(untitled) (Raparin Journal of Humanities (RJH), 2022)
Enlightenment as an intellectual concept is the result of the perspectives of many thinkers and philosophers in the western world. It has become the source of deep change in the western culture and thinking; it has also come into the eastern world and culture. Eventually, the influence of that movement arrived at the Kurdish literature and can easily be found in the works of Kurdish poets and authors. They dealt with the phenomenon in accordance with their understanding in Kurdish poems. Although the influence of the phenomenon has not reflected in the minds of the Kurdish poets, due to the inappropriate conditions of our nation, as is the case in the western world, the Kurdish poets could take advantage from the various aspects of phenomenon and renew the content of the Kurdish poetry. Enlightenment poets played an effective role in raising the awareness of Kurdish society, especially those who were aware of the innovation movement in the world and had a deep understanding of the conditions of the Kurdish society. Hence, poetry became a moving and a educating message. As a result, we see that the content of the poetry of that period has experienced a remarkable change.